Risk of repetition and subsequent self-harm following presentation to hospital with suicidal ideation: A longitudinal registry study. (June 2020) - Griffin, E.; Kavalidou, K.; Bonner, B.; O'Hagan, D.; Corcoran, P.
Abstract: Background: Few studies have focused on those who present to hospital with suicidal thoughts (suicidal ideation). The aim of this study was to establish the risk of repeat presentation to hospital following suicidal ideation and to identify factors which were associated with further ideation or subsequent self-harm. Methods: Data were obtained from the Northern Ireland Registry of Self-harm. Risk of repeat presentation following hospital-presenting ideation was analysed using Kaplan Meier analyses, specifically cox proportional hazard models. Findings: During the period April 2014 to March 2019, a total of 14, 695 presentations to hospital due to suicidal ideation were made in Northern Ireland. The cumulative incidence of repeat presentation to hospital was 40·5% within five years, with an 18·3% risk of subsequent self-harm. Previous ideation had the strongest association with repeat presentation. There was evidence of recidivism considering further ideation, with an increased risk according to number of previous presentations. In contrast, risk of subsequent self-harm was highest after the first or second presentation. Male gender and alcohol were associated with further ideation, while females and young people were more likely to re-present with self-harm. Interpretation: The findings indicate that individuals who present to hospital with suicidal ideation are at risk of repeat presentation and future self-harm, however clinical guidelines do not specifically address hospital-presenting ideation. The transition from ideation to suicidal behaviour is important to consider and research could inform effective screening and early intervention measures. Role of Funding: The Northern Ireland Registry of Self-harm is funded by the Public Health Agency, Northern Ireland.